Profile of Chief Academic Officers - Cejda, Brent D.; Rewey, Kirsten L. (Education Policy Analysis Archives, 2001)
Chief Academic Officer (CAO) is the most common position title before assuming the presidency of a college or university. Results from a national survey are used to develop a profile of the CAO in each respective Carnegie institutional classification. The typical CAO in four-year institutions is Caucasian, male, 54 years old, and married. He holds a doctoral degree, most likely in humanities or social sciences, and has held the CAO position for 5 or fewer years. Most often, the CAO served as a Dean or Associate Dean in the previous position. All CAOs have classroom experience, but 3% have never taught full-time. With only slight variances among the percentages, these characteristics are similar for each of the respective Carnegie classifications. Comparisons are also made between the characteristics of presidents and CAOs.